ViolinTalk: Violin Robots as Internet of Things Devices - Hsing-Hsin Huang; Yi-Bing Lin (IEEE Access, 2023)
In recent years, the application of intelligent robots in the field of music has gradually emerged. Among string instruments, the violin stands as an unparalleled musical marvel, representing the soprano voice. Countless composers have penned masterpieces for this cherished instrument. This paper proposes ViolinTalk, a system for controlling XY-type violin robots as Internet of Things (IoT) devices. ViolinTalk enhances the performance of robots through calibration and testing. ViolinTalk has improved the software of violin robots with an IoT-based modular design, resulting in a better development environment. In this environment, we have made key contributions, including: 1) development of two control modes for the bowing servo motors, comprising displacement-based control and time-based control; 2) utilizing bowing speed control to introduce variations in volume and tone, enriching the performance effects; 3) analyzing errors in playing speed and establishing correction parameters for future use; and 4) analyzing the robot’s mechanism to enhance its stability and durability. ViolinTalk also leverages IoT technology to facilitate seamless connections between different music instruments for ensemble performances. Multiple robots have been successfully integrated into a string orchestra, featuring two violins, one viola, and one cello, capable of performing standard chamber music.